Gravimetric and magnetic modelling of the Ceará Plateau, Brazilian Equatorial Margin - Moura, Denise Silva de (2018)
The Brazilian Equatorial Margin is a transform passive margin with long fracture zones and several seamounts, including the Ceará Plateau, as the largest one. This is a very complex and poorly known area, with very few available research data. The geophysical approach was used to achieve a better understanding, and to guide further surveys. Gravity and magnetic data from the Equant I Project, seismic published lines and previous studies were applied to make several models and analyses. The gravity and the magnetic anomaly sources seemed to be the same, related to a denser and magnetized basement. It is estimated the basement surface between 800 and 6000 m and the Mohorovičić discontinuity, which is about 22-23 km below the Ceará Plateau. It is also presented and discussed the position of the continent-ocean boundary, recognized at approximately 40 km from the continental shelf, that locate the plateau at the oceanic crust. The area of the transitional crust, with an extension of 40-50 km, represents the altered continental crust, formed during the rift phase, previous to the Atlantic Ocean. The lack of data gives some limitation to the analysis, and add some uncertainties in the results, which are discussed along this thesis.